Composing the Early Embryonic Microenvironment: Physiology and Regulation of Oviductal Secretions - Saint-Dizier, Marie (Int J Mol Sci, 2019)
The oviductal fluid is the first environment experienced by mammalian embryos at the very beginning of life. However, it has long been believed that the oviductal environment was not essential for proper embryonic development. Successful establishment of in vitro embryo production techniques (which completely bypass the oviduct) have reinforced this idea. Yet, it became evident that in vitro produced embryos differ markedly from their in vivo counterparts, and these differences are associated with lower pregnancy outcomes and more health issues after birth. Nowadays, researchers consider the oviduct as the most suitable microenvironment for early embryonic development and a substantial effort is made to understand its dynamic, species-specific functions. In this review, we touch on the origin and molecular components of the oviductal fluid in mammals, where recent progress has been made thanks to the wider use of mass spectrometry techniques. Some of the factors and processes known to regulate oviductal secretions, including the embryo itself, as well as ovulation, insemination, endogenous and exogenous hormones, and metabolic and heat stress, are summarized. Special emphasis is laid on farm animals because, owing to the availability of sample material and the economic importance of fertility in livestock husbandry, a large part of the work on this topic has been carried out in domestic animals used for dairy and/or meat production.